Penerapan Metode Certainty Factor pada Sistem Pakar Diagnosa Penyakit Kolesterol Bagi Remaja Berbasis Web - Nurfalah Nurfalah; Rouli Doharma MS (Switch : Jurnal Sains dan Teknologi Informasi, 2024)
An expert system is artificial intelligence that imitates the ability of an expert to solve problems in a certain domain. Utilizing a knowledge base and specified rules, the expert system provides advice or decisions that approach human expertise in this specific field, especially regarding cholesterol disease for teenagers, cholesterol disease can cause death in a person so it needs initial treatment as a diagnosis. In this regard, an expert system application is needed to diagnose cholesterol disease for users which supports the diagnosis process using the certainty factor method, based on the certainty factor which has a concept based on symptoms and diagnosis from the weight of an expert's value and the user's value, then calculated using the certainty factor formula, The final result is the creation of an expert system application for diagnosing cholesterol disease using a website-based certainty factor method.